2001
DOI: 10.2223/jped.243
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate dehydrogenase deficiency with recurrent infections: case report

Abstract: ResumoObjetivo: relatar a ocorrência de uma deficiência funcional de neutrófilos rara, com quadro clínico e laboratorial semelhante ao da doença granulomatosa crônica.Métodos: relato de caso de paciente com deficiência acentuada da glicose-6-fosfato desidrogenase e infecções de repetição. Realizada pesquisa bibliográfica utilizando as bases de dados Medline e Lilacs, abrangendo o período de 1972 a 2000.Resultados: paciente com nível da glicose-6-fosfato desidrogenase extremamente reduzido e quadro de infeções … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In Brazil, G6PDd was suggested to contribute to haemolysis in patients with the viscerocutaneous form of loxoscelism, a condition produced by the bite of the recluse spiders of genus Loxosceles [ 118 ]. In Brazil, there have been reports of recurrent infections in children diagnosed with G6PDd [ 119 , 120 ]. In contrast, increased rates of urinary tract infections and neonatal jaundice were not substantiated among pregnant women from Puerto Rico, Dominican Republic, Mexico and other Caribbean areas living in the United States.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, G6PDd was suggested to contribute to haemolysis in patients with the viscerocutaneous form of loxoscelism, a condition produced by the bite of the recluse spiders of genus Loxosceles [ 118 ]. In Brazil, there have been reports of recurrent infections in children diagnosed with G6PDd [ 119 , 120 ]. In contrast, increased rates of urinary tract infections and neonatal jaundice were not substantiated among pregnant women from Puerto Rico, Dominican Republic, Mexico and other Caribbean areas living in the United States.…”
Section: Resultsmentioning
confidence: 99%
“…One of the primary mechanisms of host immune responses in combating C. violaceum infection is by antimicrobial activities of neutrophils via expression of superoxide dismutase enzyme and the release of reactive oxygen species (ROS) (14). G6PD is essential in maintaining redox equilibrium of cellular NADPH that results in the production of ROS, including hydrogen peroxide (H 2 O 2 ), for killing pathogens (14). Microorganisms also produce H 2 O 2 from their metabolic processes, which the host cells can utilize to fight against infection.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this pathway is a key component of innate immunity and is modulated by systemic inflammation. For example, it has been shown that changes in the oxidative burst capacity are associated with various autoimmune diseases such as multiple sclerosis, arthritis, and recurrent infections 10,11 . Currently there are no high throughput quantitative assays available to measure the oxidative burst in clinical samples.…”
Section: Introductionmentioning
confidence: 99%